Enabling exercise prescription for survivors of cancer - Katherine R. White (Nature Portfolio, 2021)
Abstract Although exercise is widely recommended for survivors of cancer, readily implementable approaches for evaluating exercise tolerance enabling exercise prescriptions at appropriate levels of cardiovascular exertion are not always available. We evaluated the utility of modified Harvard Step tests within the context of a standard physical examination for fitness evaluation and exercise prescription for survivors of cancer across a range of age, BMI and exercise history. While 52% of presenting individuals with a past cancer diagnosis were able to complete a 3-min test at pace with a reduced 9-in. step, adoption of self-determined pacing, test duration and completion on a flat surface enabled relative fitness rating and appropriate exercise prescription for the remaining survivors. Younger age and more vigorous exercise histories correlated with completion of the standard 3-min test at pace, but all 9-in. formats led to exercise prescriptions more vigorous than current activity. The physical examination setting expedited inclusion of core and specific muscle group strength testing. The approach is adaptable to a range of health care settings, providers, and patients, providing a shared opportunity for providers and patients to evaluate exercise tolerance. It can be used to further expand incorporation of exercise testing and prescription into routine care.